(untitled) (Contemporary Journal of Social Science Review, 2025)
This research looks at how childhood trauma influences the actions and behaviors of adults living in Lahore, Pakistan. In this study researcher trying to understand is how forms of childhood trauma such as emotional abuse and neglect of care lead to changes in people’s behavior, emotions and methods of coping once they are adults. Quantitative and structured questionnaires were given to 200 adults between ages 25 and 45 chosen from a specific group. Data were analyzed with statistical techniques including measures of central tendency, correlations and regression analysis. Based on the research, a clear relation is established between distress in childhood and experiencing anxiety, aggression, difficulties with trust and social withdrawal as an adult. In the study, it is shown that early traumatic events can harm a person’s psychology and behaviors over time which is why quick action and support programs are needed in both schools and hospitals.